南極ドームふじ基地における接地気温逆転層の観測的特徴 - 平沢, 尚彦; Naohiko, Hirasawa (2013)
Dome Fuji station includes typical inland characteristics and carries an important role as the representative of a part of the continent on understanding climate of Antarctica in cooperation with some inland stations. The purpose of the present paper is to describe the characteristics of surface-based temperature inversion observed at Dome Fuji station through all the seasons of 1997, including polar night, summer, and the transient period from winter to summer. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object